On the Probabilities of Environmental Extremes - Kedem, Benjamin; Stauffer, Ryan M.; Zhang, Xuze; Pyne, Saumyadipta (International Journal of Statistics in Medical Research, 2021)
Environmental researchers, as well as epidemiologists, often encounter the problem of determining the probability of exceeding a high threshold of a variable of interest based on observations that are much smaller than the threshold. Moreover, the data available for that task may only be of moderate size. This generic problem is addressed by repeatedly fusing the real data numerous times with synthetic computer-generated samples. The threshold probability of interest is approximated by certain subsequences created by an iterative algorithm that gives precise estimates. The method is illustrated using environmental data including monitoring data of nitrogen dioxide levels in the air